Restoring Australia’s Freshwater Wetlands: Rural Landholder Perspectives - Elizabeth P Galanis; Lai Ming Lam; Lukas Schuster; Damien Cook; Martino E Malerba (Wetlands, 2026)
Wetlands are among the most productive and biodiverse ecosystems in the world, yet they are also the most threatened. These vital habitats play a crucial role in mitigating climate change. Although most freshwater wetlands occur on private property, limited research exists on landholder perceptions of their ownership and management. We interviewed landholders who participated in a wetland restoration program. Our interviews explored motivations and barriers to participation and the impact of climate change, if any, on landholders. We conducted a thematic analysis of interview transcripts. Our analysis revealed three major themes. First, participants were motivated by the intrinsic value of nature, focusing on benefits to native flora and fauna rather than personal gain. They expressed strong emotional connections to nature and a sense of stewardship. Second, the removal of bureaucratic, financial and practical barriers by a knowledgeable local facilitator was important for participation. Third, participants acknowledged the tension between agricultural practices and the needs of nature, striving to balance these competing demands. Although climate change was recognised, the primary motivator was restoring natural ecosystems. Restoring freshwater wetlands can help policymakers achieve international and domestic biodiversity goals by aligning conservation programs with landholders’ values. Employing local facilitators with intimate knowledge of the community and ecosystem can enhance program engagement. Additionally, integrating agricultural and environmental needs, such as through agritourism, can further support biodiversity, and the economic and mental resilience of landholders.